Global poverty : global governance and poor people in the post-2015 era - Hulme, David (London ; New York : Routledge/Taylor & Francis, 2015)
"The first book to tackle the issue of global poverty through the lens of global institutions; this fully updated volume provides an important resource for all students and scholars of international relations, development studies and international political economy"--
Includes bibliographical references and index.
Keywords: Poverty -- International cooperation; Poverty -- Government policy; International organization